Essential Hypertension: An Approach to Its Etiology and Neurogenic Pathophysiology - Juan J. Bolívar (International Journal of Hypertension)
Essential hypertension, a rise in blood pressure of undetermined cause, includes 90% of all hypertensive cases and is a highly important public health challenge that remains, however, a major modifiable cause of morbidity and mortality. This review emphasizes that, from an evolutionary point of view, we are adapted to ingest and excrete <1 g of sodium (2.5 g of salt) per day and that essential hypertension develops when the kidneys become unable to excrete the amount of sodium ingested, unless blood pressure is increased. The renal-mean arterial pressure set-point model is briefly described to explain that a shift of the pressure natriuresis relationship toward abnormally high pressure levels is a pathophysiological characteristic of essential hypertension. Evidence indicating that this anomaly in the pressure natriuresis relationship arises from a sympathetic nervous system dysfunction is briefly formulated, and the most widely accepted pathophysiologic proposal to explain the development of this sympathetic dysfunction is described, with commentaries about novel action mechanisms of some drugs currently used in essential hypertension treatment.